Motherhood, respectability & baby-farming in Victorian & Edwardian London - Stuart-Bennett, Joshua G. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Motherhood, Respectability & Baby-Farming in Victorian & Edwardian London explores the largely obscured marketplace of motherhood that provided ways for women to manage the stigma of illegitimacy and their respectable identities within Victorian and Edwardian society. It focuses on the extent of women's 'dirty work', when maternal problem management was fundamental to the general maintenance of respectability and, by extension, to Empire and Civilisation. Despite its intrigue, history has struggled to understand and represent an uncomfortable but significant artifact of Western modernising society: 'baby-farming'. During a period when ideologies of respectability and civilisation arguably mattered most, the 'right' kind of parenthood - especially motherhood - became paramount. As the 'wrong' offspring could jeopardise a woman's chances of being respectable, a wholesale, informal, and somewhat clandestine marketplace emerged that catered to various maternal difficulties. Within this marketplace, a pregnancy or new-born child who may have compromised a woman's respectability could be 'disposed' of through different means, for a fee. From the Victorian period to the present, the commercialised maternal practices associated with baby-farming have become firmly established within collective consciousness as being synonymous with child murder, female pathology, and 'infanticide for hire'. This book provides a revised, far more complex, and nuanced narrative history which reveals all that was associated with baby-farming - including all possible outcomes - to be entirely natural, rational, and even necessary products of their time; an understandable outcome of the period's 'civilising offensive'. Motherhood, Respectability & Baby-Farming in Victorian & Edwardian London will be of great interest to students and scholars of criminology, sociology, history, and gender studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Motherhood -- Social aspects -- England -- London -- History -- 19th century; Motherhood -- Social aspects -- England -- London -- History -- 20th century; Baby-farming -- England -- London -- History -- 19th century; Baby-farming -- England -- London -- History -- 20th century; Infants -- Abuse of -- England -- London -- History -- 19th century; Infants -- Abuse of -- England -- London -- History -- 20th century